Sistem Pendukung Keputusan Pemberian Beasiswa Kurang Mampu di SMA Negeri 2 Kupang Menggunakan Metode Profile Matching - Da Costa, Jonia Nova; Priadana, Adri; Al Badawi, M. Abu Amar (Jurnal Teknomatika, 2020)
At SMAN 2 Kupang, the scholarship program for underprivileged students greatly contributes to their educational attainment. Scholarships at SMAN 2 Kupang are awarded based on parents/guardians' income, number of dependents, possession of smart Indonesian cards, and disabilities. However, there is often an issue of inaccurate scholarship distribution. Some students who do not meet the eligibility criteria receive scholarships, while deserving students who are less fortunate do not receive them. To address this problem, we propose a scholarship decision support system utilizing the profile matching method as the calculation algorithm. The system is developed using the PHP programming language and MySQL database. The primary benefit of this system is to assist in the scholarship selection process based on predetermined criteria. The system includes student registration, profile matching calculation, and the ability to generate registration and calculation reports.